Factors associated with employment status before and during pregnancy: Implications for studies of pregnancy outcomes. Issue 4 (April 2017) - Rocheleau, Carissa M.; Bertke, Stephen J.; Lawson, Christina C.; Romitti, Paul A.; Desrosiers, Tania A.; Agopian, Aaron J.; Bell, Erin; Gilboa, Suzanne M.; ,
Abstract: Background: Potential confounding or effect modification by employment status is frequently overlooked in pregnancy outcome studies. Methods: To characterize how employed and non‐employed women differ, we compared demographics, behaviors, and reproductive histories by maternal employment status for 8, 343 mothers of control (non‐malformed) infants in the National Birth Defects Prevention Study (1997–2007) and developed a multivariable model for employment status anytime during pregnancy and the 3 months before conception. Results: Sixteen factors were independently associated with employment before or during pregnancy, including: maternal age, pre‐pregnancy body mass index, pregnancy intention, periconceptional/first trimester smoking and alcohol consumption, and household income. Conclusions: Employment status was significantly associated with many common risk factors for adverse pregnancy outcomes. Pregnancy outcome studies should consider adjustment or stratification by employment status. In studies of occupational exposures, these differences may cause uncontrollable confounding if non‐employed women are treated as unexposed instead of excluded from analysis. Am. J. Ind. Med. 60:329–341, 2017. © 2017 Wiley Periodicals, Inc.